Persepsi Wisatawan Terhadap Citra Kepariwisataan Di Kawasan Titik Nol Kilometer Yogyakarta Pasca Revitalisasi - Astriecia, Aisha; Budiyono, Nararya Rahadyan (JURNAL DESTINASI PARIWISATA, 2020)
Zero Kilometre Yogyakarta is one of the tourism destination icons of Yogyakarta. From visitors’ perspectives, this destination is claimed to be the most unique one in Yogyakarta due to the multifunctional usages of the spot. Furthermore, Zero Kilometre Yogyakarta is not only used as a cultural destination, but also utilized as an interesting public space in the city. The present study aims to delineate the visitors’ perceptions about the Zero Kilometre as one of Yogyakarta’s tourist destination icons after its revitalization project. For this purposes, observation, questionnaires, and interviews were used as the data collection techniques. Moreover, the Slovin formula was utilized to determine 100 participants (57 woman and 43 men) who were randomly selected in the present study. As the data is the in form of quantitative, then the differential semantic charts were utilized for further analysis. The findings of the present study indicate that the visitors ‘perceptions about Zero Kilometre Yogyakarta 56 percent of respondent stated this area as Zero Kilometre Yogyakarta. Data from semantic differential graphic also shown positive line tendential. In fact, the revitalization project brings about positive perceptions among the visitors as they view the project has made the Zero Kilometre Yogyakarta as the most interesting spot as one of cultural tourism destinations in town.   Keyword : perception, tourist, destination, image, culture